High-Volume Upcycling of Waste Sediment and Enhancement Mechanisms in Blended Grouting Material - Luchen Zhang; Xuena Jia; Guanjie Yang; Deming Wang (Advances in Materials Science and Engineering)
Waste sediment (WS) is a solid waste produced from subway construction. In the present work, high-volume WS was upcycled to prepare grouting material.The results showed that the working performances (consistency, fluidity, setting time, bleeding ratio, and stone ratio)of WS-based grouting material were significantly affected by the mass concentration of solid components, binder to WS ratio, and steel slag addition. This material can meet the engineering requirement by adjusting these parameters. The WS-based grouting material exhibited superior performance compared to traditional grouting materials. It achieved self-leveling (160 mm fluidity) and wassuitable for grouting (consistency within 100-130 mm, 95.0% stone ratio). Amorphous phases were formed in the hardened sample. The addition of a suitable amount of steel slag (10%) can reduce the total porosity, and also promote the hydration degree and increase the mechanical properties of cement matrix.The strength development can be attributed to the formation of hydration products and the cementation between hydrates and sediment particles.